Biofilm formation on different pH conditions by Streptococcus agalactiae isolated from bovine mastitic milk. (10th July 2018) - Miranda, P.S.D.; Lannes‐Costa, P.S.; Pimentel, B.A.S.; Silva, L.G.; Ferreira‐Carvalho, B.T.; Menezes, G.C.; Mattos‐Guaraldi, A.L.; Hirata, R.; Mota, R.A.; Nagao, P.E.
Abstract: Streptococcus agalactiae is among the most relevant aetiologic agent of bovine clinical and subclinical mastitis, a major problem for the dairy industry. In Brazil, clonal diversity, capsular typing and multidrug resistance profiles of S. agalactiae related to human and bovine infections need further investigation. Presently, S. agalactiae isolates of bovine subclinical mastitis, from Brazilian Northeastern region, were submitted to capsular and pulsed‐field gel electrophoresis (PFGE)‐typing, antimicrobial susceptibility and assays of biofilm formation at different time incubation and pH levels. Sixteen bovine isolates were characterized by polymerase chain reaction assay as S. agalactiae capsular type II (CTII) and classified by PFGE in A1/A2 ( n = 06), B1/B2 ( n = 06), C ( n = 03) and D ( n = 01) patterns. Bovine S. agalactiae CTII strains were classified as 25% multidrug‐resistant (MDR) with susceptibility to penicillin, linezolid and vancomycin. Biofilm formation on abiotic surface was strain‐ and time‐dependent with significantly higher rates at pH 6·5. In conclusion, S. agalactiae capsular type II isolates recovered from bovine subclinical mastitis produced different pH‐dependent biofilm levels. Our findings suggest that biofilm production is modulated by environmental factors and provides S. agalactiae advantageous in colonizing mammary gland during mastitis development, including MDR strains. Significance and Impact of the Study: Streptococcus agalactiae is among the most relevant aetiologic agent of bovine clinical and subclinical mastitis, a major problem for the dairy industry. The disease may cause significant economic loss due to decreased production and milk quality and increased use of medicaments. Presently, data demonstrated that biofilm formation favours the establishment of infectious process in health mammary tissue by S. agalactiae and emphasizes that an acidic pH promotes adhesion by biofilm‐forming bacterial strains. S. agalactiae strains (25%) showed resistance to tetracycline, azithromycin, erythromycin and clindamycin, and consequently were classified as multidrug‐resistant strains. Significance and Impact of the Study: Streptococcus agalactiae is among the most relevant aetiologic agent of bovine clinical and subclinical mastitis, a major problem for the dairy industry. The disease may cause significant economic loss due to decreased production and milk quality and increased use of medicaments. Presently, data demonstrated that biofilm formation favours the establishment of infectious process in health mammary tissue by S. agalactiae and emphasizes that an acidic pH promotes adhesion by biofilm‐forming bacterial strains. S. agalactiae strains (25%) showed resistance to tetracycline, azithromycin, erythromycin and clindamycin, and consequently were classified as multidrug‐resistant strains.